IMPLEMENTATION PECULIARITIES OF THE “AUTHOR’S CHAIR” AS A MODERN TEACHING METHOD - ARZUMANYAN, ARMENUHI (Main Issues Of Pedagogy And Psychology, 2013)
The distinctive feature of the “Author’s Chair” as a teaching method is that the student who has carried out the research work presents the systematized subject method from the “Author’s Chair” as the author of the theme. This fact makes him/her feel deeper sense of responsibility towards the task.